1988
DOI: 10.1016/0014-5793(88)81434-0
|View full text |Cite
|
Sign up to set email alerts
|

Does the channel for nascent peptide exist inside the ribosome? Immune electron microscopy study

Abstract: MS2 phage RNA-directed synthesis of an N-terminal polypeptide of the phage coat protein on Escherichia coli 70 S ribosomes was initiated in a cell-free system with the N-dinitrophenyl derivative of methionyltRNAp and performed in the absence of tyrosine, lysine, cysteine and methionine. As a result, the translating ribosomes carried peptides up to 42 amino acid residues in length with the dinitrophenyl hapten at the N-ends. Using the immune electron microscopy technique the positions of the nascent peptide N-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 24 publications
(2 reference statements)
3
29
0
2
Order By: Relevance
“…It presumes that a nascent polypeptide chain can fold immediately at the peptidyltransferase center of the ribosome and no intraribosomal tunnel exists, as was indicated previously (61)(62)(63).…”
Section: Shorter ␣-Globin Peptides Of 75 65 and 34 Amino Acid Residmentioning
confidence: 55%
“…It presumes that a nascent polypeptide chain can fold immediately at the peptidyltransferase center of the ribosome and no intraribosomal tunnel exists, as was indicated previously (61)(62)(63).…”
Section: Shorter ␣-Globin Peptides Of 75 65 and 34 Amino Acid Residmentioning
confidence: 55%
“…However, the tunnel seems spacious enough to impose no restrictions to the sequence of the growing peptides and may accommodate amino acids to which bulky groups, such as biotin, have been bound (23). In recent immuno electron microscopy experiments, the N-termini of nascent chains were detected in two locations: one close to the subunit interface, where the end of short polypeptides were detected, and the second at the other end of the particle (34), where the N-termini of longer chains were found. Further studies indicated that ribosomes protect natural proteins more efficiently than artificial homo polymers (21) and that the latter may choose a path slightly different from that chosen by naturally occurring proteins (16).…”
Section: Approximate Shapes 0/ the Ribosomal Subunits Within The Assementioning
confidence: 99%
“…Perhaps the context-complexity of the critical leader peptide region is combinatorial in nature and acts by placing two amino acid side chains, four residues apart, in apposition on the same face of an alpha-helix. Such an interpretation would follow from models proposed by Yonath et al (59) and Ryabova et al (43), according to which the first few amino acids in the nascent peptide are confined to a tunnel or channel in which they assume, at least temporarily, an alpha-helical conformation. Moreover, the apparent ineffectiveness of amino acid alterations at Gly-2 and Ile-3 (fMGIFSIFVISTV-) at influencing induction is consistent with the conclusions of Contreras and Vazquez (8) and of Vazquez (51a) that erythromycin only affects synthesis of the growing peptide chain after it has reached a critical length of two to five residues.…”
mentioning
confidence: 96%